Diverse Routes of Allograft Tolerance Disruption by Memory T Cells - Gill, Ronald G.; Burrack, Adam L. (Frontiers in Immunology, 2020)
Memory T lymphocytes constitute a significant problem in tissue and organ transplantation due their contribution to early rejection and their relative resistance to tolerance-promoting therapies. Memory cells generated by environmental antigen exposure, as with T cells in general, harbor a high frequency of T cell receptors (TCR) spontaneously cross-reacting with allogeneic major histocompatibility complex (MHC) molecules. This phenomenon, known as ‘heterologous’ immunity, is thought to be a key barrier to transplant tolerance induction since such memory cells can potentially react directly with essentially any prospective allograft. In this review, we describe two additional concepts that expand this commonly held view of how memory cells contribute to transplant immunity and tolerance disruption. Firstly, autoimmunity is an additional response that can comprise an endogenously generated form of heterologous alloimmunity. However, unlike heterologous immunity generated as a byproduct of indiscriminate antigen sensitization, autoimmunity can generate T cells that have the unusual potential to interact with the graft either through the recognition of graft-bearing autoantigens or by their cross-reactive (heterologous) alloimmune specificity to MHC molecules. Moreover, we describe an additional pathway, independent of significant heterologous immunity, whereby immune memory to vaccine- or pathogen-induced antigens also may impair tolerance induction. This latter form of immune recognition indirectly disrupts tolerance by the licensing of naïve alloreactive T cells by vaccine/pathogen directed memory cells recognizing the same antigen-presenting cell in vivo. Thus, there appear to be recognition pathways beyond typical heterologous immunity through which memory T cells can directly or indirectly impact allograft immunity and tolerance.